Reorientasi Gerakan Feminisme Islam; Sebuah Upaya Membangun Kesetaraan Perempuan - WARITS, ABD (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2016)
In the history of women's life, the woman has never cracked from the wild cry of helplessness. Woman always become victim of men’s egoism, marginalized, hurt, unfettered, fooled and never appreciated the presence and role. This situation troubles many intellectual Muslims who have perspective that Islam teaches equality, equality for all human beings in the world. The difference in skin color, race, tribe and nation, as well as gender does not cause them to get the status of the different rights and obligations. The potential and the right to life of every human being and the obligation to serve the Lord Almighty is the same. Indeed, all human beings, as caliph in the world, have the same obligation, namely to prosperity of life in the world. No one is allowed to act arbitrarily, destroying, or hurt among others. They are required to live side by side, united, and harmonious, help each other and respect each other. However, that